Survey on the Potency of Cow Milk Dangke as an Alternative to Buffalo Milk Dangke in Enrekang, South Sulawesi - W. Hatta; M. B. Sudarwanto; I. Sudirman; R. Malaka (Jurnal Ilmu dan Teknologi Peternakan, 2013)
The scarcity of buffalo milk caused farmers in Enrekang district switch to use cow's milk as a raw material for the manufacture of dangke. This study aims to explore the potential of dangke milk cows from various aspects in the field.  Information on population and daily milk production of dairy cows and buffalo, as well as questionnaire data of dangke consumers of Enrekang were obtained in Enrekang district, while data of dangke consumer of not Enrekang were collected with organoleptic tests and questionnaires. Determination of respondents Enrekang with simple random sampling while respondents are not Enrekang with purposive sampling.  Data were analyzed by descriptive statistics, independent two-sample t test and chi squared test. The potential benefits of cow milk dangke compared to cow buffalo dangke is that with the same quality (moisture, fat, protein, ash, and pH value) cow’s milk dangke has higher raw material availability, cheaper price, easier attainability, widely accepted by Enrekang consumer population, preferred by the non-Enrekang consumer population, and also possess colour and flavor that is preferred by consumers.